2017
DOI: 10.1111/iej.12877
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of irrigant activation techniques in removing intracanal smear layer and debris from mature permanent teeth: a systematic review and meta‐analysis

Abstract: Virdee SS, Seymour DW, Farnell D, Bhamra G, Bhakta S. Efficacy of irrigant activation techniques in removing intracanal smear layer and debris from mature permanent teeth: a systematic review and meta-analysis. International Endodontic Journal.Aims To establish whether irrigant activation techniques (IATs) result in greater intracanal smear layer and debris removal than conventional needle irrigation (CNI). Methodology Six electronic databases were searched to identify scanning electron microscopy studies eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
95
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 68 publications
1
95
0
7
Order By: Relevance
“…A recent meta‐analysis on intracanal smear layer and debris removal concluded that irrigant activation techniques such as sonic or ultrasonic activation resulted in greater smear layer and debris removal than conventional manual irrigation across a substantial portion of the canal (Virdee et al . ). However, cleanliness in isthmuses was not evaluated and comparison of findings therefore remains speculative.…”
Section: Discussionmentioning
confidence: 97%
“…A recent meta‐analysis on intracanal smear layer and debris removal concluded that irrigant activation techniques such as sonic or ultrasonic activation resulted in greater smear layer and debris removal than conventional manual irrigation across a substantial portion of the canal (Virdee et al . ). However, cleanliness in isthmuses was not evaluated and comparison of findings therefore remains speculative.…”
Section: Discussionmentioning
confidence: 97%
“…The aforementioned limitations of CNI could, however, be overcome through the use of irrigant activation techniques. Manual dynamic activation (MDA), passive ultrasonic irrigation (PUI) and sonic irrigation (SI) are currently some of the most widely used and studied methods (Gu et al 2009, Virdee et al 2018). MDA involves repeatedly inserting a well‐fitting gutta‐percha (GP) cone to the working length of an instrumented canal to produce hydrodynamic displacing forces within irrigants (McGill et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, accumulation of debris is a potential side effect of root canal instrumentation and may result in an inefficient seal of root canal fillings and, in cases with apical periodontitis, reduces the probability of healing . Therefore, irrigation with antimicrobial and tissue‐dissolving solutions and activation of the irrigant are crucial for thorough disinfection of the entire root canal system .…”
Section: Introductionmentioning
confidence: 99%